Crowdsourcing: personal values and self-efficacy as antecedents to creative behavior - Morais, Susana (2013)
Creative crowdsourcing and crowdsourcing for innovation initiatives (hereinafter called CCI) are a business model that allows companies to leverage the crowd’s skills and know-how through online platforms where the individuals (solvers) voluntarily supply them with ideas and solutions. CCI initiatives are similar to open contests and depend heavily on submissions that actually solve the posted challenges. Despite the frequent use of incentives (financial and others) CCI dynamics relies above all on the individuals’ predisposition and motivations. Understanding the impact of personal values and self-efficacy on this kind of initiatives will decrease the level of uncertainty caused by the lack of any previously relation, link or contact between the companies and the solvers (which are anonymous). Certain studies point to a correlation among some values and self-efficacy with creativity. While it is difficult to change personal values, self-efficacy is a well-documented approach to change behaviors. In order to answer the research question “How do the motivational antecedents affect the participants’ creative behavior in CCI initiatives?” the research will pursue the following topics: - assess solvers’ values; - evaluate their self-efficacy levels; - establish connections between the solvers’ values and self-efficacy. Given the need to capture the phenomena as a whole this investigation will adopt a qualitative approach based on netnography methodology. Considering the research question and the theoretical background based on values and self-efficacy, it will adopt a preliminary step comprising an anonymous online questionnaire issued to creative solvers. The research will follow with online interviews hoping to seize the interviewees’ experiences, in order to draw all possible insights related with their CCI initiatives engagement.